Investigation of Mg(2+)- and temperature-dependent folding of the hairpin ribozyme by photo-crosslinking: effects of photo-crosslinker tether length and chemistry - Borda, Emily J. (Oxford University Press, 2005)
We have used photo-crosslinking to investigate the structure and dynamics of four-way junction hairpin ribozyme constructs. Four phenylazide photo-crosslinkers were coupled to 2′-NH(2)-modified U+2 in the substrate and irradiated at different Mg(2+) concentrations and temperatures. Consistent with the role of divalent metal ions in hairpin ribozyme folding, we observed more interdomain crosslinks in the presence of Mg(2+) than in its absence. In general, we observed intradomain crosslinks to nucleotides 2–11 and interdomain crosslinks to the U1A binding loop. Crosslinks to A26 and G36 in domain B were also observed when crosslinking was carried out at −78°C. In contrast to crosslinking results at higher temperatures (0, 25 and 37°C), similar crosslinks were obtained in the presence and absence of Mg(2+) at −78°C, suggesting Mg(2+) stabilizes a low-energy hairpin ribozyme conformation. We also evaluated the effects of photo-crosslinker structure and mechanism on crosslinks. First, most crosslinks were to unpaired nucleotides. Second, shorter and longer photo-crosslinkers formed crosslinks to intradomain locations nearer to and farther from photo-crosslinker modification, respectively. Finally, fluorine substitutions on the phenylazide ring did not change the locations of crosslinks, but rather decreased crosslinking efficiency. These findings have implications for the use of phenylazide photo-crosslinkers in structural studies of RNA.